2020
DOI: 10.1186/s13019-020-01362-1
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of mitral valve repair for atrial functional mitral regurgitation: a retrospective study

Abstract: Background Annular dilation by left atrial remodeling is considered the main cause of atrial function mitral regurgitation. Although acceptable outcomes have been obtained using mitral ring annuloplasty alone for atrial functional mitral regurgitation, data assessing outcomes of this procedure are limited. Therefore, we aimed to assess midterm outcomes of mitral valve repair in patients with atrial functional mitral regurgitation. Methods We retrospectively studied 40 patients (mean age: 69 ± 9 years) who ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…We added reinforcement of the rough zone by artificial chordae implantation using the loop technique to the pseudo-prolapsed area to avoid recurrent prolapse [ 23 , 26 ]. Kaneyuki et al reported mid-term results of mitral repair in 40 cases [ 27 ]. They applied artificial chordae replacement to the anterior leaflet for pseudo-prolapse in 19 (19%) patients, and 2 patients developed moderate to severe MR during follow-up.…”
Section: Surgical Strategies For Pseudo-prolapse Of the Anterior Leafletmentioning
confidence: 99%
See 1 more Smart Citation
“…We added reinforcement of the rough zone by artificial chordae implantation using the loop technique to the pseudo-prolapsed area to avoid recurrent prolapse [ 23 , 26 ]. Kaneyuki et al reported mid-term results of mitral repair in 40 cases [ 27 ]. They applied artificial chordae replacement to the anterior leaflet for pseudo-prolapse in 19 (19%) patients, and 2 patients developed moderate to severe MR during follow-up.…”
Section: Surgical Strategies For Pseudo-prolapse Of the Anterior Leafletmentioning
confidence: 99%
“…In our previous study, we added TAP to all surgical cases of atrial functional MR, even if TR was less than moderate to prevent regurgitation from worsening in the future [ 23 ]. Kaneyuki et al reported that three patients developed moderate or severe recurrent TR during follow-up in five patients without TAP [ 27 ]. These authors suggested that TAP should be performed in addition to mitral valve repair of atrial functional MR. Balogh et al added TAP in 67 (49%) patients, but they did not mention postoperative TR [ 24 ].…”
Section: Tricuspid Valve Repair As a Treatment For Dual-valve Diseasementioning
confidence: 99%